The Influence of Compensation, Non-Physical Work Environment, and Work–Life Balance on Employee Loyalty - Nur Jihan Aliya; Aris Wahyu Kuncoro (Golden Ratio of Data in Summary, 2026)
This study examines the influence of compensation, non-physical work environment, and work–life balance on team member loyalty at PT: Pancar Surya Mandiri Perkasa, a private security services company based in South Tangerang. Adopting a quantitative explanatory approach, the research involved 48 employees selected through a saturated sampling technique, ensuring full population coverage. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed through multiple linear regression (MLR). Reliability and validity tests were conducted to ensure instrument consistency. The findings indicate that compensation has a significant positive effect on employee loyalty, reflecting that fair and performance-based rewards enhance employees’ commitment. Likewise, a supportive non-physical work environment—characterized by open communication, trust, and psychological safety—significantly strengthens employee loyalty. Moreover, work–life balance contributes positively by maintaining harmony between professional and personal domains, leading to stronger attachment and reduced turnover intention. These results underscore the importance of implementing comprehensive human resource management strategies that integrate equitable compensation, supportive work culture, and balanced workload arrangements to enhance employee retention and organizational sustainability in labor-intensive industries.